Antioxidant Supplements May Yield Undesired Outcomes - Joudi, Fawwaz S. Al (Current Advances in Chemistry and Biochemistry Vol. 2, 2021)
The escalating use of antioxidant supplements has been questioned repeatedly although the potential side effects of antioxidants have neither been adequately assessed nor understood. This work represents a comprehensive insight into the literature seeking potential targets of antioxidants in tissues and cells, with which they would interact to produce their toxic effects. Oxidants are cellular components that drive some cellular key metabolic processes in cancer cells, yet they appear to weaken certain other metabolic pathways in the same cells. Excess deactivation by antioxidants may enhance cellular survival through abating apoptotic pathways and enhancing energy production from glycolysis. Furthermore, oxidants are important effectors of immune reactivity as well as metabolic activators of the immune cells that carry out anti-microbial and anti-tumoral activities, hence, abolishing oxidant activity may hinder these vital functions. It is hypothesized that the critical balance of oxidants-antioxidants can be disrupted by excessive antioxidant consumption, setting a new state of “antioxidant stress”, leading to enhanced growth of cancer cells and to compromised immunity. A critical balance of antioxidants intake needs to be assessed for the clinical situation. In addition, the potential molecular mechanisms that may lead to this stress have been thoroughly explored.